Slave lawsuits in the Spanish Supreme Court and Overseas, demanding their freedom - López Santamaría, Ramsés (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
This article seeks to locate decisions that closed judicial processes on requests for freedom by slaves, in the use of the appeal and within the framework of the judicial and legal structure originating in Spain. This scenario warns an aspect of interest in the sense of proving how close the arguments that were given in the Spanish Supreme Court could become with respect to those that arose in the cases resolved on the same subject by the judges located in the territories of the Viceroyalty of New Granada. For this case, a documentary analysis of primary and secondary references related to the state of the question is proposed.